2013
DOI: 10.1080/00071668.2013.797954
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of nutrient equivalency of microbial phytase in hens in late lay given maize–soybean or distiller's dried grains with solubles (DDGS) diets

Abstract: 1. An experiment was conducted with 360 Lohmann LSL-Classic White Leghorn layers (64 weeks old) to evaluate the effects of supplementation of microbial phytase on production, egg quality, bone, selected manure parameters and feed costs. 2. Experimental diets were formulated as follows: (1) maize-soybean (CS), (2) CS+300 units of phytase (FTU)/kg diet which was formulated to recoup only calcium and available phosphorus equivalency for phytase (CS+PHYCa+P), (3) CS+300 FTU/kg diet which was formulated to recoup t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 36 publications
0
3
0
2
Order By: Relevance
“…One of the objectives to adding exogenous enzymes to poultry feed is to hydrolyze the fraction that chickens cannot efficiently digest, as the fiber and phytate. Nonstarch polysaccharide degrading enzymes ( Liu et al, 2011 ; Romero et al, 2013 ; Campasino et al, 2015 ) and phytase ( Olukosi et al, 2010 ; Deniz et al, 2013 ) have been shown to improve nutrients digestibility in corn DDGS diets. However, in the present work, we added a multicarbohydrase (xylanase, β-glucanase, ABF) and phytase complex to the diets and despite the positive performance effects the MCPC inclusion did not affect nutrient digestibility.…”
Section: Discussionmentioning
confidence: 99%
“…One of the objectives to adding exogenous enzymes to poultry feed is to hydrolyze the fraction that chickens cannot efficiently digest, as the fiber and phytate. Nonstarch polysaccharide degrading enzymes ( Liu et al, 2011 ; Romero et al, 2013 ; Campasino et al, 2015 ) and phytase ( Olukosi et al, 2010 ; Deniz et al, 2013 ) have been shown to improve nutrients digestibility in corn DDGS diets. However, in the present work, we added a multicarbohydrase (xylanase, β-glucanase, ABF) and phytase complex to the diets and despite the positive performance effects the MCPC inclusion did not affect nutrient digestibility.…”
Section: Discussionmentioning
confidence: 99%
“…В литературе отмечают неодинаковую эффективность разных препаратов фитаз (28)(29)(30)(31). Обобщая результаты своего эксперимента, мы можем констатировать, что оба отечественных фитазных препарата (Фидбест-Р и Берзайм-Р) при добавлении в комбикорма для бройлеров позволяют снизить дозу неорганического фосфора в рационе, повышая при этом продуктивность птицы.…”
Section: значения индексов биоразнообразия микроорганизмов в слепых оunclassified
“…The authors observed increased P digestibility and bone mineralisation in chickens when a diet with 30% DDGS was supplemented with phytase. A positive effect of phytase in laying hens fed a diet with 10% cDDGS was reflected in improved FI and FCR, as well as a decrease in P content in manure (Deniz et al., ). However, Koksal et al.…”
Section: The Effects Of Phytasementioning
confidence: 99%